Method for modifying top slag after oxygen blowing decarburization of ultra-low-carbon low-silicon steel RH (Ruhrstahl Heraeus) vacuum furnace

By adding an Al-quality modified agent to reduce the oxygen content according to the color of the top slag after blowing and decarbonizing in the RH vacuum furnace, the problem of high oxidation of the top slag is solved, and the TFe control in the modified slag is achieved within a suitable range, ensuring good conductivity of the casting billet and the stability of continuous casting.

CN119614793APending Publication Date: 2025-03-14SGIS SONGSHAN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411875511.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When producing ultra-low carbon series steel, after the RH vacuum furnace blows oxygen and decarbonizes, the FeO and MnO content in the top slag is high, resulting in a large amount of oxygen being transferred to the steel after the pouring of the steel, affecting the cleanliness of the steel. In severe cases, it will cause current storage and make it difficult to achieve multi-furnace continuous casting.

Method used

According to the color of the top slag after the steel is blown and decarbonized in the RH vacuum furnace, an Al-quality modified agent is added to reduce the oxygen content in the top slag, so that the TFe in the modified slag is controlled within the range of 2.0-4.0%.

Benefits of technology

By rapidly reducing the oxygen content in the top slag, the Al2O3 inclusions in the molten steel are reduced, the cleanliness of the molten steel is affected, the chance of nodules in the water mouth during continuous casting is reduced, and the casting billet is ensured is good electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614793A_ABST
    Figure CN119614793A_ABST
Patent Text Reader

Abstract

The invention discloses a method for modifying top slag after oxygen blowing decarburization of an ultra-low-carbon low-silicon steel RH (Ruhrstahl Heraeus) vacuum furnace. The method comprises the step of adding an Al modifier to reduce the oxygen content in top slag according to the color of the top slag after oxygen blowing decarburization of molten steel in an RH vacuum furnace. The inventor summarizes a method for judging oxidability before and after top slag modification and a modifier addition amount algorithm through practice, after top slag modification is completed, TFe in slag is in the range of 2.0-4.0%, the probability of nozzle nodulation in molten steel continuous casting is small, a produced casting blank does not have the bubble defect affecting the steel quality, and the conductivity of steel is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a method for modifying top slag after oxygen blowing decarburization in an ultra-low carbon and low silicon steel RH vacuum furnace. Background Art

[0002] When using the "converter-argon station-RH-continuous casting" process to produce ultra-low carbon steel grades, the top slag of the ladle cannot be fully reduced like LF refining, so the FeO and MnO content in the slag is very high after RH refining. The top slag of the ladle is still highly oxidizing slag. In the late stage of molten steel pouring during continuous casting, a large amount of oxygen in the slag is transferred to the molten steel, reacting with Als in the steel to produce a large amount of Al 2 O 3 Inclusions affect the cleanliness of molten steel and in severe cases may cause current accumulation, making it difficult to achieve continuous casting of multiple furnaces. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the above technical background and provide a method for modifying the top slag after oxygen blowing decarburization of ultra-low carbon and low silicon steel RH vacuum furnace.

[0004] The invention provides a method for modifying top slag after oxygen decarburization in an RH vacuum furnace for ultra-low carbon and low silicon steel. The method comprises: adding an Al-based modifier to reduce the oxygen content in the top slag according to the color of the top slag after oxygen decarburization in the RH vacuum furnace for molten steel.

[0005] The present invention has the following beneficial effects.

[0006] The present invention provides a method for modifying the top slag after oxygen decarburization in an RH vacuum furnace of ultra-low carbon and low silicon steel, which comprises: according to the color of the top slag after oxygen decarburization in the RH vacuum furnace, an Al-based modifier is added to reduce the oxygen content in the top slag. In the process of modifying the top slag, the modification needs to be completed in a relatively short time, and the time from sampling to completion of the inspection by slag sample analysis is usually relatively long, and it is not possible to wait for the slag sample test results to determine the oxidizability of the top slag. According to the color of the top slag after oxygen decarburization in the RH vacuum furnace, the inventor adds an Al-based modifier to reduce the oxygen content in the top slag, so that the TFe in the modified slag is within the range of 2.0-4.0%, so that the oxygen content of the modified top slag meets the requirements, the probability of nozzle nodules in the subsequent continuous casting of the molten steel is small, the produced ingots have no bubble defects that affect the quality of the steel, and the electrical conductivity of the steel is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0008] Figure 1 This is the appearance of the top slag in the RH vacuum furnace before modification in Example 1;

[0009] Figure 2 This is the appearance of the top slag after modification in the RH vacuum furnace in Example 1;

[0010] Figure 3 This is the appearance of the steel billet prepared in Comparative Example 2. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0012] The following is a specific description of a method for modifying top slag after oxygen decarburization in an ultra-low carbon and low silicon steel RH vacuum furnace provided by an embodiment of the present invention.

[0013] The embodiment of the present invention provides a method for modifying top slag after oxygen decarburization of ultra-low carbon low silicon steel in an RH vacuum furnace, which comprises: adding Al quality modifier to reduce the oxygen content in the top slag according to the color of the top slag after oxygen decarburization of molten steel in an RH vacuum furnace.

[0014] In order to improve the conductivity of ultra-low carbon, low silicon steel wire products used in the preparation of cables, the lower the other components except Fe, the better, among which C≤0.008%, Si≤0.008%, Als≤0.005%. In the production of ultra-low carbon, low silicon steel, the molten steel must be treated by oxygen blowing and decarburization in an RH vacuum furnace. Since the blown oxygen is partially absorbed by the ladle top slag, the ladle top slag must be modified to reduce the oxidizability of the slag and avoid the oxygen in the slag after the RH treatment of the molten steel returning to the molten steel, resulting in subcutaneous blistering defects in the produced ingots. At the same time, the SiO in the slag during the ladle top slag modification process must be reduced. 2 Reduction increases the Si content in molten steel and affects the electrical conductivity of the steel.

[0015] At present, the top slag modification method and steps are as follows: after the molten steel is decarburized, deoxidized and vacuumed at the RH station, the top slag thickness is measured, a special modifier is manually added to the slag surface, and a large ladle is opened for low-level argon blowing and weak stirring for 2 to 4 minutes to promote the top slag to fully react with the modifier to reduce the FeO content in the slag. After modification, the slag sample is taken for component analysis to determine whether the oxygen content in the modified top slag meets the requirements. Given that the slag sample analysis takes more than 8 minutes from sampling to completion of the inspection, and the top slag modification needs to be completed within 5 minutes, it is impossible to wait for the slag sample test results to determine the top slag oxidizability.

[0016] In order to solve the above problems, the embodiment of the present invention provides a method for modifying the top slag after oxygen decarburization in an RH vacuum furnace for ultra-low carbon and low silicon steel. The inventor has summarized a method for judging the oxidizability of the top slag before and after modification through practice. The method includes: adding Al-based modifier to reduce the oxygen content in the top slag according to the color of the top slag after oxygen decarburization of molten steel in an RH vacuum furnace. The method can quickly determine the amount of modifier added and achieve the control of TFe in the modified slag within a suitable range of 2.0 to 4.0%, so that the smelting can be carried out stably and continuously.

[0017] In some optional embodiments, it includes: when the top slag color is black after oxygen decarburization of molten steel in RH vacuum furnace, Al quality modifier with aluminum content of 30-50% is manually added to the slag surface to reduce the oxygen content in the top slag. The top slag color is black after oxygen decarburization of molten steel in RH vacuum furnace, indicating that the slag is highly oxidizable, and Al quality modifier needs to be added to the slag surface to promote the top slag to fully react with the modifier to reduce the FeO content in the slag.

[0018] In some optional embodiments, the following operations are performed before the top slag modification: slag is prevented during the converter steel-making process, less slag refining is adopted in the LF refining process, only lime is added to make slag, and aluminum-containing deoxidizer is used for diffusion and precipitation deoxidation. 2 The Si content in the molten steel is increased by reducing the top slag during the RH treatment process. In the LF refining process, low-slag refining is adopted and only lime is added to make slag to reduce the increase of Si in the molten steel during the RH treatment process. Aluminum-containing deoxidizer is used for diffusion and precipitation deoxidation to reduce the amount of refined slag.

[0019] In some optional implementations, the top slag modification includes: determining the amount of the Al-based modifier based on the number of oxygen blowing operations in the RH vacuum furnace, the dissolved oxygen content of the molten steel after oxygen blowing and decarburization, and the top slag thickness.

[0020] In some optional implementations, the top slag modification steps are as follows: after the molten steel is decarburized by blowing oxygen in the RH vacuum furnace, a steel sample is taken to analyze the C content, the dissolved oxygen content of the molten steel is measured with an oxygen meter, and an aluminum-containing deoxidizer is added for deoxidation. After the molten steel is decarburized and deoxidized and the vacuum is broken, the top slag thickness is measured, an Al-based modifier is manually added to the slag surface, and argon is blown from the bottom of the ladle for weak stirring to perform top slag modification.

[0021] In some optional embodiments, the main components of the Al-based modifier are: Al: 35-60%, Al 2 O 3 :20~50%, CaO: 10~30%, SO 2 :≤7.0%, modifier particle size 5~30mm.

[0022] In some optional embodiments, the molten steel is decarburized and oxygen is blown in the RH vacuum furnace for at least 1 time and at most 3 times. After the molten steel is decarburized by oxygen blowing in the RH vacuum furnace, the dissolved oxygen content does not exceed 650ppm and the carbon content does not exceed 0.003%. Then, an aluminum-containing deoxidizer is added to deoxidize the molten steel until the residual dissolved oxygen is within the range of 20-40ppm. When the residual dissolved oxygen in the molten steel is lower than 20ppm, the Als in the steel will exceed the upper limit of the steel grade control, the fluidity of the molten steel will deteriorate, causing nodules at the continuous casting nozzle, and the SiO2 in the ladle top slag will increase. 2 Reduced Si-enriched molten steel. When the residual dissolved oxygen in the molten steel is higher than 40ppm, subcutaneous bubbles will appear in the produced ingot. The top slag of oxygen decarburization absorbs part of the oxygen, and the oxidizing property increases, so the top slag needs to be modified.

[0023] In some optional embodiments, the amount of the modifier added is as follows:

[0024] Based on 120 tons of converter steel liquid, oxygen is blown once, and the dissolved oxygen in the steel liquid after oxygen blowing and decarburization is ≤350ppm. The slag before modification is black or dark green, the slag layer thickness is 180mm, and the amount of modifier added is 0-30kg; for each additional oxygen blowing, 20kg of modifier is added, and for each additional 50ppm of dissolved oxygen content, 25ppm≤dissolved oxygen content≤50ppm is calculated as 50ppm, and when the dissolved oxygen content is <25ppm, it is calculated as 0, and 10kg more of modifier is added; the slag layer thickness is based on 180mm, and for each increase or decrease of 10mm, 5mm≤slag layer thickness<10mm is calculated as 5mm, and when <5mm is calculated as 0, the amount of modifier added is increased or decreased by 10kg accordingly. When the top slag before modification is black slag, the amount of modifier added should be not less than 20kg when the slag layer thickness is less than 180mm.

[0025] In some optional implementations, the method further includes: after the top slag modification is completed, a top slag sample is taken with a steel rod, knocked on the ground, and after cooling to 200-600°C, the oxidizability of the slag is judged by observing the color of the slag. When the color of the modified top slag is dark green, the oxygen content in the modified top slag meets the requirements. When the color of the modified top slag is dark green, TFe is 2.0-4.0%, and the oxygen content in the top slag meets the requirements. When the TFe content is 1.5-2.0%, the SiO in the top slag is 0.1%. 2 Reduced Si, the Si in molten steel has the risk of exceeding the upper limit of steel grade control. When the TFe content is less than 1.5%, the SiO in the top slag 2 When the TFe content is between 4.0% and 4.5%, the top slag is highly oxidizing, and the oxygen in the modified slag will return to the steel through the steel-slag interface reaction. The produced ingot has the risk of producing subcutaneous bubbles. When the TFe content is greater than 4.5%, the top slag is highly oxidizing, and the produced ingot will have subcutaneous bubble defects.

[0026] In some optional embodiments, after the top slag is modified, the TFe content in the top slag is in the range of 1.6-4.2%, and the TFe content in the range of 2.0-4.0% accounts for more than 96%, the probability of nozzle nodules in continuous casting is small, the produced ingots are free of bubble defects, and the ultra-low carbon and low-silicon steel products have good electrical conductivity.

[0027] The present invention will be further described below in conjunction with the embodiments.

[0028] The test method of the electrical conductivity of steel in the following examples and comparative examples can refer to the measurement method given in CN201710359844.9 A method for measuring the electrical conductivity of hot-rolled wire rod for copper-clad steel. The special modifier used is an Al-based modifier, which mainly consists of: Al: 44.8%, Al 2 O 3 :28.6%, CaO: 16.5%, SO 2 : 6.3%, modifier particle size 5 ~ 30mm.

[0029] Example 1

[0030] 120 tons converter smelting ultra-low carbon low silicon steel, the production process is converter smelting → LF furnace refining → RH furnace vacuum treatment → 160×160mm 2 Billet continuous casting.

[0031] After the molten steel was decarburized twice by oxygen blowing in the RH furnace, the C content of the steel sample was 0.0018%. The dissolved oxygen in the molten steel was 473ppm measured by an oxygen meter. After adding 85kg aluminum in two batches for deoxidation, the dissolved oxygen in the molten steel was 32ppm. After breaking the vacuum, the top slag thickness was measured by a steel rod and was 175mm. After the slag was cooled, the slag color was black. See Figure 1 The left picture shows the appearance of the top slag sample after being taken with a steel rod and knocked on the ground after cooling. The right picture shows the top slag peeled off from the steel rod after cooling. 50kg of special modifier is thrown to the slag surface by hand, and a large ladle is opened to blow argon gas weakly for 3 minutes. The top slag sample is taken with a steel rod and knocked on the ground after cooling. The color of the slag is as follows Figure 2 It is dark green in color, and the oxidizability of the top slag after modification is greatly reduced. The results of slag sample analysis show that the TFe content is 2.6%.

[0032] After the RH treatment, the steel sample analysis results showed C 0.0018%, Si 0.005%, the smelting composition sample analysis results showed C 0.0043%, Si 0.006%, and other components met the steel grade control requirements. The surface quality of the produced ingots and wires was normal, without defects such as bubbles and cracks. The electrical conductivity of the steel was measured to be 17.2%.

[0033] Example 2

[0034] 120 tons converter smelting ultra-low carbon low silicon steel, the production process is converter smelting → LF furnace refining → RH furnace vacuum treatment → 160×160mm 2 Billet continuous casting.

[0035] After the molten steel was decarburized by oxygen blowing once in the RH furnace, a steel sample was taken for analysis and the C content was 0.002%. The dissolved oxygen in the molten steel was measured to be 606ppm using an oxygen meter. After adding 106kg of aluminum in three batches for deoxidation, the dissolved oxygen in the molten steel was measured to be 21ppm. After breaking the vacuum, the top slag thickness was measured to be 190mm using a steel rod. The slag was black in color after cooling. 70kg of special modifier was thrown onto the slag surface by hand, and a large ladle was opened for low argon blowing and weak stirring for 3 minutes. The top slag sample was taken with a steel rod and the cooled slag was dark green when knocked on the ground. The slag sample analysis results showed that the TFe content was 2.1%.

[0036] After the RH treatment, the steel sample analysis results showed C 0.0026%, Si 0.007%, the continuous casting smelting composition sample analysis results showed C 0.0055%, Si 0.007%, and other components met the steel grade control requirements. The surface quality of the produced ingots and wires was normal, without defects such as bubbles and cracks. The electrical conductivity of the steel was measured to be 16.8%.

[0037] Example 3

[0038] 120 tons converter smelting ultra-low carbon low silicon steel, the production process is converter smelting → LF furnace refining → RH furnace vacuum treatment → 160×160mm 2 Billet continuous casting.

[0039] After the molten steel was decarburized by oxygen blowing once in the RH furnace, the C content of the steel sample was analyzed to be 0.003%. The dissolved oxygen in the molten steel was measured to be 325ppm using an oxygen meter. After adding 67kg of aluminum in two batches for deoxidation, the dissolved oxygen in the molten steel was measured to be 29ppm. After breaking the vacuum, the top slag thickness was measured to be 168mm using a steel rod. After the slag was knocked on the ground and cooled, it turned dark green. No modifier was added, and the TFe content of the slag sample analysis results was 3.8%.

[0040] After the RH treatment, the steel sample analysis results showed C 0.0033%, Si 0.005%, the smelting composition sample analysis results showed C 0.0065%, Si 0.005%, and other components met the steel grade control requirements. The surface quality of the produced ingots and wires was normal, without defects such as bubbles and cracks. The electrical conductivity of the steel was measured to be 17.0%.

[0041] Example 4

[0042] 120 tons converter smelting ultra-low carbon low silicon steel, the production process is converter smelting → LF furnace refining → RH furnace vacuum treatment → 160×160mm 2 Billet continuous casting.

[0043] After the molten steel was decarburized by oxygen blowing for three times in the RH furnace, the C content of the steel sample was analyzed and it was 0.0015%. The dissolved oxygen in the molten steel was measured to be 525ppm with an oxygen meter. After adding 92kg of aluminum in three batches for deoxidation, the dissolved oxygen in the molten steel was measured to be 26ppm. After breaking the vacuum, the top slag thickness was measured with a steel rod and it was 183mm. The slag was black in color after cooling. 90kg of special modifier was thrown onto the slag surface by hand, and a large ladle was opened for low argon blowing and weak stirring for 3 minutes. The top slag sample was taken with a steel rod and the cooled slag was dark green when knocked on the ground. The slag sample analysis results showed that the TFe content was 3.2%.

[0044] After the RH treatment, the steel sample analysis results showed C 0.0016%, Si 0.004%, the smelting composition sample analysis results showed C 0.004%, Si 0.005%, and other components met the steel grade control requirements. The surface quality of the produced ingots and wires was normal, without defects such as bubbles and cracks. The electrical conductivity of the steel was measured to be 17.3%.

[0045] Comparative Example 1

[0046] The same steelmaking equipment and process flow as in Implementation 1 are used to produce ultra-low carbon, low silicon steel.

[0047] After the molten steel was decarburized by oxygen blowing once in the RH furnace, a steel sample was taken for analysis, and the C content was 0.0025%. The dissolved oxygen result of the molten steel was 506ppm. After adding 89kg of aluminum in two batches for deoxidation, the dissolved oxygen in the molten steel was measured to be 31ppm. After breaking the vacuum, the top slag thickness was measured to be 195mm. 50kg of special modifier was thrown onto the slag surface by hand, and a large ladle was opened for low argon blowing and weak stirring for 3 minutes. The top slag sample was taken with a steel rod, knocked on the ground for cooling, and then the slag sample was taken for analysis, and the TFe content was 1.4%.

[0048] After the RH treatment, the steel sample analysis results showed C 0.0042%, Si 0.008%, and the smelting composition sample analysis results showed C 0.0058%, Si 0.0092%. The Si content exceeded the upper limit of the steel grade. The conductivity of the produced wire was measured to be 15.8%, and the conductivity did not meet the requirements.

[0049] Comparative Example 2

[0050] The same steelmaking equipment and process flow as in Implementation 1 are used to produce ultra-low carbon, low silicon steel.

[0051] After the molten steel was decarburized by oxygen blowing twice in the RH furnace, a steel sample was taken for analysis, and the C content was 0.0019%. The dissolved oxygen result of the molten steel was 536ppm. After adding 95kg of aluminum for deoxidation in two batches, the dissolved oxygen in the molten steel was measured to be 25ppm. After breaking the vacuum, the top slag thickness was measured to be 205mm. 80kg of special modifier was thrown onto the slag surface by hand, and a large ladle was opened for low argon blowing and weak stirring for 3 minutes. The top slag sample was taken with a steel rod, and the slag color was black after knocking it on the ground for cooling. The slag sample was taken for analysis, and the TFe content was 4.8%.

[0052] Continuous casting slab pickling inspection Figure 3 As shown, there are obvious bubble defects and intermittent crack defects on the surface of the rolled steel.

[0053] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for modifying top slag after oxygen decarburization in an ultra-low carbon and low silicon steel RH vacuum furnace, characterized in that: It includes: According to the color of the top slag after oxygen decarburization of molten steel in the RH vacuum furnace, Al-based modifier is added to reduce the oxygen content in the top slag.

2. The top slag modification method according to claim 1, characterized in that: It includes: When the top slag is black in color after oxygen decarburization of molten steel in the RH vacuum furnace, an Al-based modifier with an aluminum content of 30 to 50% is manually added to the slag surface to reduce the oxygen content in the top slag.

3. The top slag modification method according to claim 1 or 2, characterized in that: The following operations are performed before top slag modification: slag is prevented during the converter tapping process; low-slag refining is adopted in the LF refining process, only lime is added to form slag, and aluminum-containing deoxidizer is used for diffusion and precipitation deoxidation.

4. The top slag modification method according to claim 1 or 2, characterized in that: The top slag modification comprises: determining the amount of Al quality modifier according to the number of oxygen blowing in the RH vacuum furnace, the dissolved oxygen content of molten steel after oxygen blowing and decarburization, and the top slag thickness.

5. The top slag modification method according to claim 4, characterized in that: The steps of top slag modification are as follows: after the molten steel is decarburized by blowing oxygen in the RH vacuum furnace, take a steel sample to analyze the C content, use an oxygen meter to measure the dissolved oxygen content of the molten steel, add aluminum-containing deoxidizer for deoxidation, and measure the top slag thickness after the molten steel is decarburized and deoxidized and the vacuum is broken. Manually add Al-quality modifier to the slag surface, open the bottom of the large ladle to blow argon for weak stirring, and perform top slag modification.

6. The top slag modification method according to claim 5, characterized in that: The main components of the Al-based modifier are: Al: 35-60%, Al2O3: 20-50%, CaO: 10-30%, SO2: ≤7.0%, and the modifier particle size is 5-30 mm.

7. The top slag modification method according to claim 5, characterized in that: The molten steel is decarburized and oxygen-blown in the RH vacuum furnace at least once and at most three times. After the molten steel is decarburized by oxygen-blowing in the RH vacuum furnace, the dissolved oxygen content does not exceed 650ppm and the carbon content does not exceed 0.003%. Then, an aluminum-containing deoxidizer is added to deoxidize until the residual dissolved oxygen in the molten steel is within the range of 20-40ppm.

8. The top slag modification method according to claim 5, characterized in that: The addition amount of the Al quality modifier is as follows: Based on 120 tons of converter steel liquid, oxygen is blown once, and the dissolved oxygen in the steel liquid after oxygen blowing and decarburization is ≤350ppm. The slag before modification is black or dark green, the slag layer thickness is 180mm, and the amount of modifier added is 0-30kg; for each additional oxygen blowing, 20kg of modifier is added, and for each additional 50ppm of dissolved oxygen content, 25ppm≤dissolved oxygen content≤50ppm is calculated as 50ppm, and when the dissolved oxygen content is <25ppm, it is calculated as 0, and 10kg more of modifier is added; the slag layer thickness is based on 180mm, and for each increase or decrease of 10mm, 5mm≤slag layer thickness<10mm is calculated as 5mm, and when <5mm is calculated as 0, the amount of modifier added is increased or decreased by 10kg accordingly. When the top slag before modification is black slag, the amount of modifier added should be not less than 20kg when the slag layer thickness is less than 180mm.

9. The top slag modification method according to claim 6, characterized in that: Also includes: After the top slag modification is completed, use a steel rod to take a top slag sample, knock it on the ground, and after cooling to 200-600℃, judge the oxidizability of the slag by observing the color of the slag. When the color of the modified top slag is dark green, the oxygen content in the modified top slag meets the requirements.

10. The top slag modification method according to any one of claims 5 to 9, characterized in that: After top slag modification, the TFe content in the top slag is in the range of 1.6-4.2%, and the TFe content in the range of 2.0-4.0% accounts for more than 96%. The probability of nozzle nodules in continuous casting is small, the produced ingots have no bubble defects, and the ultra-low carbon and low-silicon steel products have good electrical conductivity.

Citation Information

Patent Citations

  • Method for measuring electrical conductivity of hot rolled wire rod for copper-clad steel

    CN108957134A